Pengaruh Kepemimpinan, Iklim Organisasi, dan Motivasi Kerja Terhadap Kinerja Karyawan di Sekolah Tinggi Ilmu Kesehatan (STIKes) Wira Medika Bali - Ni Putu Marini; I Made Sumada; A. A. Rai Sita Laksmi (Universitas Warmadewa, 2017)
Leaders influence subordinates and subordinates can influence leaders and Climate organizations affect the practice of HR policies received by members of the organization. Human resources (HR) is one of the main factors in the competition in the global era, so must think how to create quality human resources and have skills and high competitive in competition. In the globalization of intraregional and international relations there will be competition between countries. Given the magnitude of the role of leaders as a driver of the institution in achieving its goals, then the leadership effort to encourage employees to work better. The purpose of this research is to know the influence of leadership variable to employee performance variable, influence from organizational climate variable, influence from work motivation variable to employee performance variable, simultaneous influence from leadership variable, organizational climate, and work motivation to employee performance variable at STIKes Wira Medika Bali. The type of data needed is primary data and secondary data from HR and document STIKes Wira Medika Bali. Research Results The results show that leadership has a very strong influence on performance. Leadership has a very strong influence (0,900) based on the results of correlation test on employee performance in STIKes Wira Medika Bali with coefficient value 0,468 at probability 0.000. The probability value is less than alpha (5%). Climate Organization has a strong influence (0.788) based on the correlation test on employee performance in STIKes Wira Medika Bali with coefficient value 0.261 on probability 0.001. The probability value is less than alpha (5%). Motivation has a moderate effect (0,572) based on correlation test on employee performance in STIKes Wira Medika Bali with coefficient value 0,106 at probability 0.004. The probability value is less than alpha (5%). Leadership, organizational climate and motivation simultaneously affect the performance of employees in STIKes Wira Medika Bali seen from the value of F arithmetic of 381.125 with probability value (sig value) 0.000.0 with coefficient of determination of 0.961 or 96.1%. This means that as much as 96.1% of performance is explained by leadership variables, organizational climate, and work motivation. While the remaining 3.9% is explained by other variables outside the variable leadership, organizational climate, and work motivation.